Pengaruh Inflasi, BI Rate dan Nilai Tukar Mata Uang Asing Terhadap Profitabilitas Bank Syariah Indonesia - Husen, Muhammad Saddam; Fahlevi, Rizal (At-Tamwil: Journal of Islamic Economics and Finance, 2024)
This researchs aims to analyze the ef ect of Inflation, BI Rate and Foreign Exchange Rates on the Profitability (ROA) of Bank Syariah Indonesia in. The sample in this study was taken based on the monthly financial statements of Bank Syariah Indonesia. In this study using quantitative methods and tested based on normality test, multicollinearity test, heteroscedasticity test and autocorrelation test, it can be stated that the research data meet the classical assumptions. The results of the study partially show that the inflation variable and the BI Rate have a positive but not significant ef ect on profitability at Bank Syariah Indonesia. Meanwhile, the foreign currency exchange rate variable has a positive and significant ef ect on profitability at Syariah Mandiri banks. This coef icient of determination states that the magnitude of the influence of inflation, BI Rate and foreign currency exchange rates is 37.0% and the rest is influenced by other variables of 63, 0% which is not in the regression model of this study.